Investigating culture an experiential introduction to anthropology - Delaney, Carol Lowery 1940-; Kaspin, Deborah (Wiley-Blackwell, 2017)
"Offers a refreshing alternative to introductory anthropology texts by challenging students to think in new ways and apply cultural learnings to their own lives".